O tema da paz perpétua - Almeida, Rafael Salatini de [UNESP] (My University, 2013)
This paper presents an analytical study of the theory of perpetual peace, examining its various formulations from sixteenth century to nineteenth century, especially the Enlightenment theories of Saint-Pierre, Rousseau, Bentham and Kant, and nineteenth-century criticism of Hegel, Marx and Engels.

O texto apresenta um estudo analítico da teoria da paz perpétua, examinando suas diversas formulações do século XVI ao século XIX, em especial as teorias iluministas de Saint-Pierre, Rousseau, Bentham e Kant, e as críticas oitocentistas de Hegel, Marx e Engels.
The Perpetual Peace Theme
Keywords: paz; paz perpétua; federalismo